2008
DOI: 10.1111/j.1365-2494.2008.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Milk‐production potential of different sward types in a temperate southern Australian environment

Abstract: SummaryThe milk-production potential of different sward types was measured in each of the four seasons of the year in a replicated experiment in south-west Victoria, Australia. Dairy cows were offered ad libitum allowances of a 'short-term winter' sward, based on Italian ryegrass (treatment STW), a 'long-term winter' sward, based on a winter-active tall fescue (treatment LTW), a 'longterm summer' sward, based on a summer-active tall fescue (treatment LTS) and a Control sward (perennial ryegrass) in four season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 24 publications
6
34
1
Order By: Relevance
“…In our experiment, the positive effect of the presence of chicory on pasture DM intake suggests that the negative effect of chicory's low DM concentration is largely compensated by the positive effect of the low NDF concentration or any other component on daily intake. This is in line with several previous studies, where intake and/or milk production have been found to increase when chicory was included in mixed pastures and fed to dairy cows, either at grazing (Chapman et al, 2008;Totty et al, 2013) or indoors (Barry, 1998;Minnee et al, 2012). The increase in milk production after inclusion of chicory in the diet generally ranges from 1 to 2 kg/day, but an increase in milk production as high as 6 kg/day has been observed for cows grazing clover-chicory mixtures in summer when compared with low-quality grass-based pastures (Chapman et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our experiment, the positive effect of the presence of chicory on pasture DM intake suggests that the negative effect of chicory's low DM concentration is largely compensated by the positive effect of the low NDF concentration or any other component on daily intake. This is in line with several previous studies, where intake and/or milk production have been found to increase when chicory was included in mixed pastures and fed to dairy cows, either at grazing (Chapman et al, 2008;Totty et al, 2013) or indoors (Barry, 1998;Minnee et al, 2012). The increase in milk production after inclusion of chicory in the diet generally ranges from 1 to 2 kg/day, but an increase in milk production as high as 6 kg/day has been observed for cows grazing clover-chicory mixtures in summer when compared with low-quality grass-based pastures (Chapman et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with several previous studies, where intake and/or milk production have been found to increase when chicory was included in mixed pastures and fed to dairy cows, either at grazing (Chapman et al, 2008;Totty et al, 2013) or indoors (Barry, 1998;Minnee et al, 2012). The increase in milk production after inclusion of chicory in the diet generally ranges from 1 to 2 kg/day, but an increase in milk production as high as 6 kg/day has been observed for cows grazing clover-chicory mixtures in summer when compared with low-quality grass-based pastures (Chapman et al, 2008). Advantages of MSS on milk production and milk solids production were clearly due to the cumulative effect of improved pasture chemical composition and higher pasture DM intake.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations